Local Policies and the European Social Fund : Employment Policies Across Europe - Zimmermann, Katharina (Book collections on Project MUSE., 2020)
Comparing data from 18 local case studies across 6 European countries, and deploying an innovative mixed-method approach, this book presents comparative evidence on everyday challenges in the context of the European Social Fund (ESF) and discusses how these findings are applicable to other funding schemes.